Deteksi Defect Proses Produksi Sarung Menggunakan ATBM Berbasis Metode Failure Mode and Effect Analysis - Selly Nurdianti Khasanah; Nina Mahbubah; Hidayat Hidayat (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Small and medium firms are considered as the national safety net in times of crisis. UKM ACA is a medium-sized business and is recognized as a home industry that maintains sustainable quality. The purpose of this study is to identify defects and design better scenarios to improve product quality. This research begins with mapping the production process flow to identify product defects. After the product defect is obtained, the next step is to calculate the risk priority number. The study results showed three defects: the faded color with RPN 84, thread break with RPN 72, and irregular motifs with RPN 60.